Recent Advances in Porphyrin-Based Covalent Organic Frameworks for Synergistic Photodynamic and Photothermal Therapy - Cheng Qi; Jiayi Chen; Yijie Qu; Xuanxuan Luo; Weiqi Wang; Xiaohua Zheng (Pharmaceutics)
Porphyrin’s excellent biocompatibility and modifiability make it a widely studied photoactive material. However, its large π-bond conjugated structure leads to aggregation and precipitation in physiological solutions, limiting the biomedical applications of porphyrin-based photoactive materials. It has been demonstrated through research that fabricating porphyrin molecules into nanoscale covalent organic frameworks (COFs) structures can circumvent issues such as poor dispersibility resulting from hydrophobicity, thereby significantly augmenting the photoactivity of porphyrin materials. Porphyrin-based COF materials can exert combined photodynamic and photothermal effects, circumventing the limitations of photodynamic therapy (PDT) due to hypoxia and issues in photothermal therapy (PTT) from heat shock proteins or the adverse impact of excessive heat on the protein activity of normal tissue. Furthermore, the porous structure of porphyrin COFs facilitates the circulation of oxygen molecules and reactive oxygen species and promotes sufficient contact with the lesion site for therapeutic functions. This review covers recent progress regarding porphyrin-based COFs in treating malignant tumors and venous thrombosis and for antibacterial and anti-inflammatory uses via combined PDT and PTT. By summarizing relevant design strategies, ranging from molecular design to functional application, this review provides a reference basis for the enhanced phototherapy application of porphyrin-based COFs as photoactive materials. This review aims to offer valuable insights for more effective biomedical applications of porphyrin-based COFs through the synthesis of existing experimental data, thereby paving the way for their future preclinical utilization.